The Effect of Providing Reinforcement on Learning Motivation in Class XI Accounting at SMKN 1 Polewali - Sri Wahyuni; Samirah Dunakhir; Abdul Rijal (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of giving reinforcement skills by teachers on learning motivation in Financial Accounting in class XI Accounting at SMKN 1 Polewali. The variables in this study are reinforcement skills as the independent variable and learning motivation as the dependent variable. The population in this study were all 64 students in class XI Accounting at SMKN 1 Polewali for the 2022/2023 period, while the sample in this study was taken using a purposive sampling technique with a sample of 35 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive statistical analysis, instrument testing, and hypothesis testing using SPSS Version 25. Based on the results of the data analysis that has been carried out, a simple linear regression equation model is obtained Y'=31.128+0.440X, which means that each addition of 1 skill value gives reinforcement, then student learning motivation in financial accounting subjects increases by 0.440. From the results of the analysis of the coefficient of determination (r2) it was obtained that the value of r2 = 31.4%, which means that reinforcement skills contribute 31.4% to student learning motivation and the remaining 68.6% is influenced by other factors. While the results of the t-test analysis obtained a significant value of 0.000 <0.05, which means that the skill to provide reinforcement has a positive and significant effect on student learning motivation, thus the hypothesis is "accepted".